Social media and optimization of the promotion of Lake Toba tourism destinations in Indonesia - Muhammad Said Harahap; Rizal Khadafi; Effiati Juliana Hasibuan; Agung Saputra; Sigit Hardiyanto; Faizal Hamzah Lubis (Computer Science and Information Technologies, 2023)
Tourism is one of the largest contributors to Indonesia's foreign exchange earnings, surpassing taxation, energy, and gas. This study seeks to investigate the use of social media to optimize the promotion of Lake Toba as a tourist destination, which has been impacted by the COVID-19 pandemic. Using interview techniques and live field observations, it was discovered that social media, particularly the Instagram platform, play a significant role in promoting Lake Toba tourism. The Department of Culture and Tourism of the North Sumatra Province uses landscape photography as its primary promotion method, which has proved to be more effective and interesting than conventional methods such as the distribution of brochures or the use of manuals. The capture procedure and techniques for landscape photography were carried out by professional photographers in collaboration with the Department of Culture and Tourism of the North Sumatra Province. In addition to providing information, tourism_sumut's Instagram account functions as a platform to raise public awareness about Lake Toba tourism and as a promotional medium for North Sumatra's tourist attractions on an international scale. Department of Culture and Tourism of the North Sumatra Province collaborates with travel agencies and local communities to disseminate Lake Toba tourism information.